The Influence of Leadership Support and Work Environment on Employee Work Morale, Which Implications for the Quality of Public Services at the Population and Civil Registration Service of West Tanjung Jabung Regency - Nur, M. Syafruddin; Zahari, M.; Hapsara, Osrita (Dinasti Publisher, 2025)
This study aims to describe leadership support, work environment, work morale, and the quality of public services at the Population and Civil Registration Office of West Tanjung Jabung Regency. It also analyzes the influence of leadership support and the work environment on the quality of public services, both directly and indirectly through work morale. The study uses a quantitative approach with a survey method. The study population was 12,264 people served by the Population and Civil Registration Office of West Tanjung Jabung Regency, with a sample of 100 respondents determined using the Slovin formula. Data were collected through questionnaires and documentation, then analyzed using Structural Equation Modeling with Partial Least Square (SEM-PLS). The results showed that leadership support and the work environment had a positive and significant effect on employee work morale. Work morale was proven to play an important role as a mediating variable that strengthens the influence of leadership support and the work environment on the quality of public services. These findings confirm that the optimization of public services is not only determined by the procedural system, but also by managerial support and a conducive work environment. This research is expected to provide a practical contribution to the Population and Civil Registration Office of West Tanjung Jabung Regency in improving the quality of services, while enriching academic studies on the relationship between leadership, work environment, work enthusiasm, and the quality of public services